Developing a Google Form-based Instrument for Measuring the Spiritual Attitude of the Students Class XI - Eva, Farida; Widihastuti, Widihastuti; Istiyono, Edi (Jurnal Pendidikan Agama Islam, 2022)
Purpose – This study aims to construct an instrument for assessing the spiritual attitudes of moral subjects and how much the contribution of these spiritual attitudes can be applied in everyday life. Design/methods/approach – The research approach used by RnD (Research and Development) with the ADDIE (Analysis, Design, Development, Implementation and Evaluation) model. The subjects of this study were students of class XI. Data collection techniques use the Likert scale. Findings – The instrument was analyzed using Exploratory Factor Analysis (EFA); in the assessment of spiritual attitudes, there were four factors/dimensions, but the per-factor instrument variables did not correspond to the initial dimensions (obedience, thanksgiving, praying, and tasamuh) with the average value of the loading factor of each factor namely F1 = 0.650, F2 = 0.615, F3 = 0.578 and F4 = 0.774. In contrast, the instrument reliability test obtained a value of 0.705 with a high instrument category. The analysis results produce the findings by making new factors, namely tasamuh, gratitude, worship, and aqidah. Research implications/limitation – This spiritual attitude assessment can be used in all Madrasah Aliyah in Indonesia. However, due to the limitations of researchers in distributing questionnaires, this research was only conducted in Sintang Regency. Originality/value – Further research is expected to construct an assessment of the spiritual attitudes of students in terms of more specific aspects of learning and daily life.